Daya Saing dan Posisi Sektor Pangan IndonesiaMenghadapi Regional Comprehensive Economic Partnership (RCEP) - Dadan adi nugraha; Minar Ferichani; Joko Sutrisno (Perum BULOG, 2020)
This study aims to know the competitiveness of the Indonesian food sector in the market of RCEP partner countries, the competitiveness ofthe food sector of RCEP partner countries in the Indonesian market, and the position of the food sector is facing RCEP trade liberalization. The analysis method used in this study is the Constant Market Share Analysis (CMSA). This study uses secondary data from UN Comtrade and the ASEAN Secretariat. Indonesian food products that have positive competitiveness in the markets of RCEP partner countries are mostly processed products such as bread, biscuits, instant noodles, pasta, margarine, and vegetable oil.RCEP partner countries that have competitiveness in the Indonesian market consist of processed and fresh food products such as meat, rice, beans, and garlic. The position of the Indonesian food sector in utilizing RCEP’s trade cooperation is to propose the elimination of tariffs on Indonesian food products, and there are 23 products in China, five products in India, 16 products in Japan, and two products in Korea. The position of the Indonesian food sector in protecting the food sector from RCEP’s trade liberalization is to implement tariff policies for sensitive categories of products such as rice and sugar. Abstrak Kerja sama RCEP dipastikan akan membuka akses pasar yang luas di negara anggota RCEP. Di saat yang bersamaan Indonesia dihadapkan dengan tantangan dan ancaman apabila kerja sama RCEP diberlakukan. Tulisan ini bertujuan mengetahui daya saing produk pangan Indonesia di pasar negara mitra RCEP, mengetahui daya saing produk pangan negara mitra RCEP di pasar Indonesia, mengetahui posisi produk pangan yang dapat dimanfaatkan dan perlu dilindungi dalam rangka kerja sama perdagangan bebas RCEP. Daya saing produk pangan di analisis menggunakan Constant Market Share Analysis (CMSA). Posisi sektor pangan diketahui dengan melakukan analisis terhadap kebijakan tarif dan nilai daya saing produk pangan. Data yang digunakan adalah data sekunder yang diperoleh dari UNCOMTRADE dan Sekretariat ASEAN. Hasil analisis menunjukkan jumlah produk pangan Indonesia yang memiliki daya saing tetapi masih memiliki hambatan tarif berjumlah 23 produk di China, 5 produk di Korea, 16 produk di India, dan 2 produk di Jepang. Produk pangan Indonesia yang masih menerapkan hambatan tarif terhadap seluruh negara mitra RCEP dan perlu perlindungan tarif berjumlah 17 produk. Sedangkan produk pangan Indonesia yang sudah dihapuskan tarifnya di seluruh negara mitra RCEP berjumlah 260 produk. Produk pangan Indonesia yang memiliki hambatan tarif untuk salah satu atau lebih negara mitra RCEP berjumlah 257 produk.